2017
DOI: 10.1103/physrevb.96.134405
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural properties of FeCO3 at high pressures

Abstract: The structural and magnetic properties of siderite FeCO 3 have been studied by means of neutron powder diffraction at pressures up to 7.5 GPa and first-principles theoretical calculations. The lattice compression in the rhombohedral calcite-type structure is dominated by the reduction of the Fe-O bonds, while the changes of the C-O bonds are much less pronounced. The Néel temperature of the antiferromagnetic (AFM) ground state increases substantially under pressure with a coefficient dT N /dP = 1.8 K/GPa, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…6 ), may be explained by increased hybridization strength between the d -orbitals of Fe and p -orbitals of O atoms, leading to enhanced electronic delocalization 16 , 19 . Similar pressure-induced reduction of the ordered magnetic moment was recently also observed in the siderite FeCO 3 and underlying mechanism was evidenced by the ab-initio calculations 28 .…”
Section: Discussionsupporting
confidence: 83%
“…6 ), may be explained by increased hybridization strength between the d -orbitals of Fe and p -orbitals of O atoms, leading to enhanced electronic delocalization 16 , 19 . Similar pressure-induced reduction of the ordered magnetic moment was recently also observed in the siderite FeCO 3 and underlying mechanism was evidenced by the ab-initio calculations 28 .…”
Section: Discussionsupporting
confidence: 83%
“…In the case of FeCO 3 and FeAlO 3 , the experimental values were obtained by neutron diffraction, and in the case of FeSiO 3 , the method of Mössbauer spectroscopy was used, together with a SQUID magnetometer. For FeCO 3 , the calculated magnetic moment of iron obtained in this work is closer to an experimental value than the previous calculation [ 47 ]. For FeAlO 3 , the magnetic moment of iron reported in [ 20 ] was calculated for another crystal structure, namely, a perovskite structure.…”
Section: Discussionsupporting
confidence: 75%
“…In the regions around Fe ions in Fig. 3a, there are electrons overlaps to the adjacent oxygen, indicating the covalent contribution is seen between Fe and O atoms with the predominant of the ionic bond 27,29 .…”
Section: Stability Properties Of Corrosion Products Caused By Ca Dopingmentioning
confidence: 97%
“…Elizabeth et al 26 investigated the dolomite (CaMg(CO 3 ) 2 ) (1 0 4) phase and showed the Mg and Ca atoms have different bond distances with oxygen atoms and the main Ca-O interatomic distances turned to be greater after optimization of the surface. The analysis from Golosova et al 27 demonstrated that the anisotropic lattice compression of siderite was mainly contributed by the Fe-O bonds. Han et al 28 calculated the interactions of iron in Mg 1−x Fe x CO 3 from the iron-poor (x = 0.125) to the iron-rich (x = 1, FeCO 3 siderite) and found that the volume difference concerning MgCO 3 changes with Fe doping and resulted in the difference in relative enthalpy.…”
Section: Introductionmentioning
confidence: 99%